Aprimorando mensagens de erro geradas pela ferramenta EME - Nascimento, João Marcelo dos Santos (2025)
With the growing interest in software development, there are more and more students taking programming courses. These students tend to have great difficulties, even with the support of teachers in person and online, during practice. This is why Online Judges are such interesting tools, since they help in programming practice by providing several different questions for the most different levels and evaluating the submitted answers. Even with these tools, these beginner students still struggle when they need to understand and correct errors in the submitted source code. With this in mind, the EME tool was developed by Jesus (JESUS, 2018) and, to facilitate access to it, the FM tool was created by Rezende (REZENDE, 2024). However, even with these tools, beginner students still have difficulty understanding errors and understanding ways to get around them. To solve this, the work proposed here has evolved these tools so that they present a contextualization of each class of error in a way that can guide these students to a solution and help them understand where they are going wrong. For the evolution of EME and FM several steps were necessary and resulted in a new set of integrated tools that can further help programming students.